2017
DOI: 10.1016/j.jped.2016.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Impact and seasonality of human rhinovirus infection in hospitalized patients for two consecutive years

Abstract: HRV is usually detected in hospitalized children with respiratory infections and is often present in viral co-detections. Comorbidities are closely associated with HRV infections. These infections show seasonal variation, with predominance during colder seasons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 20 publications
(30 reference statements)
1
23
1
5
Order By: Relevance
“…The virus has also been associated with lower respiratory tract illnesses, including exacerbation of asthma and chronic obstructive pulmonary disease 5, 6 . HRV is globally ubiquitous and infections usually occur all year-round, although peaking in the early autumn and late spring in many temperate or subtropical countries, and in the rainy season in tropical countries 79 . Despite most HRV infections being mild, they pose a considerable social and economic burden due to time lost from work or school, medical attendance and reduced performance of regular duties 10 .…”
Section: Introductionmentioning
confidence: 99%
“…The virus has also been associated with lower respiratory tract illnesses, including exacerbation of asthma and chronic obstructive pulmonary disease 5, 6 . HRV is globally ubiquitous and infections usually occur all year-round, although peaking in the early autumn and late spring in many temperate or subtropical countries, and in the rainy season in tropical countries 79 . Despite most HRV infections being mild, they pose a considerable social and economic burden due to time lost from work or school, medical attendance and reduced performance of regular duties 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Em pesquisa sobre o impacto e sazonalidade da infecção por Rinovírus em pacientes internados com análise de 444 amostras respiratórias, o VSR e RV também apresentaram porcentagens muito próximas de detecção sendo 37% e 36% respectivamente [8].…”
Section: Discussionunclassified
“…Em lactentes atendidos em unidades de emergência com bronquiolite viral aguda de intensidade moderada a grave, o VSR tem papel ainda mais relevante, representando o principal agente viral isolado envolvido em admissões hospitalares e nas UTI [4]. Contudo, o RV é a causa mais comum de infecções do trato respiratório superior, porém pode também comprometer a via aérea inferior e tem sido o foco dos últimos estudos na área, devido as infecções por este agente estarem associadas a exacerbações de doenças pulmonares crônicas e pneumonia fatal em pacientes nos extremos da idade ou com comorbidades pré-existentes [8] Cada vírus apresenta uma incidência diferenciada de acordo com clima, população e região. No Brasil há relatos referentes a incidência das infecções pelos vírus [4], corroborando com os achados da presente pesquisa.…”
Section: Discussionunclassified
“…Statistically, no significant difference observed between the two percentages of coinfections. Zhang and co-workers 25 reported that a high frequency of respiratory infections and coinfections was detected in children with acute respiratory symptoms. The multiplex RT-PCR assay was also able to directly detect Piv 1+3, Piv 2+4, hAdv, and hCov.…”
Section: Fig 7: Linear and Exponential Fitting Fig 8: Scatter Diagrmentioning
confidence: 99%